Survey of public knowledge about Echinococcus multilocularis in four European countries: Need for proactive information - Romig Thomas; Gloor Sandra; Bontadina Fabio; Hegglin Daniel; Deplazes Peter; Kern Peter (BMC, 2008)
Abstract Background Public information about prevention of zoonoses should be based on the perceived problem by the public and should be adapted to regional circumstances. Growing fox populations have led to increasing concern about human alveolar echinococcosis, which is caused by the fox tapeworm Echinococcus multilocularis. In order to plan information campaigns, public knowledge about this zoonotic tapeworm was assessed. Methods By means of representative telephone interviews (N = 2041), a survey of public knowledge about the risk and the prevention of alveolar echinococcosis was carried out in the Czech Republic, France, Germany and Switzerland in 2004. Results For all five questions, significant country-specific differences were found. Fewer people had heard of E. multilocularis in the Czech Republic (14%) and France (18%) compared to Germany (63%) and Switzerland (70%). The same effect has been observed when only high endemic regions were considered (Czech Republic: 20%, France: 17%, Germany: 77%, Switzerland: 61%). In France 17% of people who knew the parasite felt themselves reasonably informed. In the other countries, the majority felt themselves reasonably informed (54-60%). The percentage that perceived E. multilocularis as a high risk ranged from 12% (Switzerland) to 43% (France). In some countries promising measures as deworming dogs (Czech Republic, Switzerland) were not recognized as prevention options. Conclusion Our results and the actual epidemiological circumstances of AE call for proactive information programs. This communication should enable the public to achieve realistic risk perception, give clear information on how people can minimize their infection risk, and prevent exaggerated reactions and anxiety.